Macrophage/microglia polarization for the treatment of diabetic retinopathy - Yao, Yujia; Li, Jiajun; Zhou, Yunfan; Wang, Suyu; Zhang, Ziran; Jiang, Qin; Li, Keran (Frontiers in Endocrinology, 2023)
Macrophages/microglia are immune system defense and homeostatic cells that develop from bone marrow progenitor cells. According to the different phenotypes and immune responses of macrophages (Th1 and Th2), the two primary categories of polarized macrophages/microglia are those conventionally activated (M1) and alternatively activated (M2). Macrophage/microglial polarization is a key regulating factor in the development of inflammatory disorders, cancers, metabolic disturbances, and neural degeneration. Macrophage/microglial polarization is involved in inflammation, oxidative stress, pathological angiogenesis, and tissue healing processes in ocular diseases, particularly in diabetic retinopathy (DR). The functional phenotypes of macrophages/microglia affect disease progression and prognosis, and thus regulate the polarization or functional phenotype of microglia at different DR stages, which may offer new concepts for individualized therapy of DR. This review summarizes the involvement of macrophage/microglia polarization in physiological situations and in the pathological process of DR, and discusses the promising role of polarization in personalized treatment of DR.